Open platform and key technology of mobile application security depth detection capability - Nishui CAI; Yirong SHI; Chenxu QIU (Dianxin kexue)
The challenges that telecom operators faced in mobile network application security monitoring services were focused on,including mobile malicious application entry,real-time monitoring and early warning,rapid blocking,timely warning,massive data processing capabilities,customized services,etc.Based on this,the telecom operator's deep application of mobile application security,the service mode of the open platform and the distributed service mode of the open platform were discussed,and the platform's current network deployment plan was put forward.